2014
DOI: 10.4049/jimmunol.1301538
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Promotes the Exacerbation of IL-33–Induced Airway Hyperresponsiveness by Enhancing Neutrophilic Inflammation via CXCR2 Signaling in Mice

Abstract: Neutrophilic airway inflammation is a hallmark of patients with severe asthma. Although we have reported that both IL-33 and IL-17A contributed to IgE-mediated neutrophilic inflammation in mice, the relationship remains unclear. In this article, we examined how IL-17A modifies IL-33–induced neutrophilic inflammation and airway hyperresponsiveness (AHR). IL-33 was intratracheally administered to BALB/c mice on days 0–2; furthermore, on day 7, the effect of the combination of IL-33 and IL-17A was evaluated. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 63 publications
9
85
0
Order By: Relevance
“…Per a 10 acts via PAR-2 receptors [8], which explains the relatively higher levels of IL-17A in the BALF of Per a 10 immunized mice. This, along with the influx of neutrophils in lungs of Per a 10 immunized mice is in accordance with previous studies where IL-17A is shown to increase neutrophilic infiltration [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Per a 10 acts via PAR-2 receptors [8], which explains the relatively higher levels of IL-17A in the BALF of Per a 10 immunized mice. This, along with the influx of neutrophils in lungs of Per a 10 immunized mice is in accordance with previous studies where IL-17A is shown to increase neutrophilic infiltration [25].…”
Section: Discussionsupporting
confidence: 93%
“…Per a 10 acts via PAR-2 receptors [8], which explains the relatively higher levels of IL-17A in the BALF of Per a 10 immunized mice. This, along with the influx of neutrophils in lungs of Per a 10 immunized mice is in accordance with previous studies where IL-17A is shown to increase neutrophilic infiltration [25].Costimulatory molecules on antigen presenting cells along with the cytokine milieu play a critical role in determining the type of T-cell response. OX40L is an important costimulatory molecule expressed on a wide variety of cells including APCs.…”
supporting
confidence: 92%
“…Steroid resistance may be attributed to activation of the STAT5 signaling pathway by TSLP, which cannot be suppressed by corticosteroids in NH cells (26). Similar to this finding, airway inflammation induced by a combined treatment with IL-33 and IL-17 was also found to be resistant to dexamethasone (19).…”
Section: Glucocorticoidssupporting
confidence: 71%
“…These two phenomena may be related to each other. IL-33-mediated airway inflammation augmented by the neutrophil-related cytokine, IL-17, could not be suppressed by dexamethasone (19).…”
Section: Asthmamentioning
confidence: 82%
“…4C). IL-17A has the capacity to induce both AHR and neutrophil recruitment (28,29,38). We and others have reported that IL-17 contributes to the AHR caused by repeated O 3 exposure in lean mice (43,44).…”
Section: Bodymentioning
confidence: 95%